The contribution of the ecozones to the ecostratigraphy. As an example the Plio - Pleistocene basin of Magoula- Karatoulas (Ilia, NE Peloponnesos) - ΣΙΝΕΚΟΓΛΟΥ Α.; ΜΑΡΚΟΠΟΥΛΟΥ-ΔΙΑΚΑΝΤΩΝΗ Α.; DRAGASTAN Ο. (Bulletin of the Geological Society of Greece, 2018)
In this paper is marked the contribution of the Ecozones to the Ecostratigraphy. As an example we use the drillings (Ml, M2, M3, M4, M6, MIO) coming from the Plio- Pleistocene basin of the Magoula- Karatoulas (Pyrgos, Peloponnesus). Based on the detailed stratigraphical and paleoecological studies of the postalpine sediments (VAGIAS et al. 1995) of the formation of Vounargo (HAGEMAN 1977,1979 & ΚΑΜΠΕΡΗΣ 1987) we attempt to define 15 ecozones, as it is understood the layer or the whole of the layers, which is characterized by an association of fossils (at the level of species, genus or family). The Ecozone reflects the evolution of a sedimentary basin from the bathymetrical point of view as well as the transgressions and the regressions. The Ecozones are often related with the curve of the change of the sea level. The transgression is characterized by the rich fossil associations (species and individuals), while the regression is characterized by a diminution of species and individuals. There are also 11 white spots, which can not be enclosed in Ecozones. They are observed in the drillings M2, M3, M4, M6 and MIO.